Circulatory and ventilatory power markers in patients with diabetes mellitus – influence of glycemic control - Menegalli Santos, Letícia; Donisete Da Silva, Claudio; Lorevice, Laura Beatriz; Italiano Monteiro, Clara; Ricci, Paula Angélica; Borghi-Silva, Audrey; Gonçalves Mendes, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. Cardiorespiratory function has been shown to be impaired in individuals with type 2 diabetes mellitus (T2DM). Some deficiencies in cardiopulmonary exercise test (CPET)-derived variables are known, however, the influence of glycemic control on cardiovascular integrity indices as circulatory power (CP) and ventilatory power (VP), deserve to be instigated. The aim was to investigate the influence of glycemic control on CP and VP indices in T2DM. Material and methods. T2DM individuals of both sexes aged between 40 and 64 years were allocated into two groups: Good glycemic control (GGC, n=11; HbA1c≤7%) and insufficient glycemic control (IGC, n=26; HbA1c>7%). All participants underwent a CPET on a treadmill using a gas analyzer and a laboratory blood test. CP values were obtained by the product of peak of oxygen uptake and systolic blood pressure (SBP) and VP by dividing SBP by the ventilatory efficiency (VE/VCO2 slope). The level of significance was set at p<0.05. Results. No baseline differences were found between the groups, except for the expected fasting glucose and glycated hemoglobin. No differences were found between GGC and IGC groups for CP (4756.05±1061.67 and 4434.15±1247.83 mmHg.ml.kg-1min-1, p=0.460) and VP (5.85±1.08 and 5.86±1.31 mmHg, p=0.978), respectively. Conclusion. CP and VP were similar in individuals with T2DM regardless of glycemic control. Predictive ability of these variables in health outcomes deserves to be further investigated in T2DM.
Keywords: cardiopulmonary exercise test; glycemic control; type 2 diabetes mellitus